O guessing game na leitura do conto literário - Amodeo, Maria Tereza; Pereira, Vera Wannmacher (Linguarum Arena, 2017)
The article focuses the guessing game (Goodman 1991; Smith 2003), on the reading of a short story, in order to achieve its comprehension. The article takes as object of study the short story “Betsy”, by Rubem Fonseca. Initially the theoretical ground is presented, associating reading and guessing game, translated as jogo de adivinhação. Hereafter, a possible metacognitive process is demonstrated considering a possible reader. Thereupon, the results of a research realized with Languages’ Course students are presented, examining their guessing paths on the reading of the same short story. In the fi nal comments, refl ections on the possibilities of this Psycholinguistics/ Literature interface and its application on teaching are made